Nanotechnology 2010
DOI: 10.1002/9783527628155.nanotech013
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Treatment, Remediation and Sensing

Abstract: Environmental pollution has become a matter of grave concern and it is clear that the issue must be dealt with early in the 21st century, before it is too late. Nanotechnology is a promising discipline that shows promise of impacting diverse fields, including environmental pollution. In this chapter, various types of environmental pollution and the scope of nanotechnology in addressing these problems are discussed. The literature on the treatment, remediation and detection (sensors) of various environmental po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…Among the drastic consequences of population explosion is the increasing contamination of drinking water resources and the century old water disinfection technique, i.e. chlorination has been found to lead to the formation of harmful disinfection byproducts (Sugunan and Dutta 2008). Research studies have shown that reaction of chlorine anions (Cl -) with organic materials suspended in water, result in the production of potentially carcinogenic by-products such as trihalomethanes and haloacetic acids (Gopal et al 2007;Sadiq and Rodriguez 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Among the drastic consequences of population explosion is the increasing contamination of drinking water resources and the century old water disinfection technique, i.e. chlorination has been found to lead to the formation of harmful disinfection byproducts (Sugunan and Dutta 2008). Research studies have shown that reaction of chlorine anions (Cl -) with organic materials suspended in water, result in the production of potentially carcinogenic by-products such as trihalomethanes and haloacetic acids (Gopal et al 2007;Sadiq and Rodriguez 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The production level of food grains is of concern as it has been showing a downward trend over the last decade. Further, extensive use of persistent chemical pesticides to boost agriculture production has also adversely affected our ecosystem and is known to have contaminated ground water [2,3]. Similarly, industrialization is leading to increase in per capita consumption of available natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, industrialization is leading to increase in per capita consumption of available natural resources. Out of 1,386 million cubic kilometers (km 3 ) of water on Earth, 97% is saline and 99.7% of the freshwater is trapped in ice caps and glaciers, or found in groundwater (one third). Only about 0.1 million km 3 of water is above ground in lakes, swamps and rivers, and about 13,000 km 3 in the atmosphere [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P HOTOCHEMICAL properties of ZnO, particularly the photocatalysis of organic compounds in water is receiving recent attention due to the severe ecological impact of various industrial and agricultural pollutants in water bodies. 1 The use of metal oxides as photocatalysts for such applications is attractive mainly due to the relatively simple photodecomposition process and their capacity to convert a large number of organic pollutant molecules into less harmful compounds. 2 Although TiO 2 (mostly anatase phase) has been extensively studied as effective photocatalyst, recently ZnO has been shown to be more effective than TiO 2 .…”
Section: Introductionmentioning
confidence: 99%